Designing A Functional Organizational Structure for Business Sustainability in A Family-Owned Garment Sme: A Case Study of Ragam Jaya Garment House - Falah, Avan Farel Al; Gustomo, Aurik (Jurnal EMT KITA, 2026)
Family-owned small and medium enterprises (SMEs) contribute significantly to economic growth; however, many encounter organizational difficulties as business activities become more complex while coordination remains informal and authority is concentrated at the top. This research focuses on Ragam Jaya Garment House, a family-run custom garment SME in Indonesia that has been operating for more than twenty years but continues to rely heavily on the owner for operational coordination and strategic decision-making. Employing an interpretive qualitative case study design, the study gathered data through semi-structured interviews, on-site observations, and reviews of internal operational records. The collected data were thematically analyzed and further evaluated using Porter’s Value Chain, the APQC Process Classification Framework, the RACI Matrix, and the Galbraith Star Model to reveal issues related to unclear role definitions, centralized decisions, unstable workflows, and coordination gaps throughout the order-to-delivery process. The findings show that operational inefficiencies are not driven by a lack of resources, but by undocumented workflows, unclear accountability, and excessive concentration of decision authority at the owner level, resulting in bottlenecks and elevated operational risk. To address these issues, the study proposes a simple functional organizational structure supported by clear decision rights and minimum process control mechanisms at critical handoff points. This design redistributes routine decisions to functional roles while retaining owner control over high-risk decisions, thereby improving coordination, reducing key-person dependency, and supporting long-term business sustainability and succession readiness.